Urban redevelopment, governance and vulnerability: thirty years of ‘regeneration’ in Dublin - Niamh Moore-Cherry (Boletín de la Asociación de Geógrafos Españoles)
Over the last three decades, state intervention through urban regeneration has focused on ‘fixing’ perceived social and spatial vulnerabilities within particular neighbourhoods, communities or city spaces but has often generated new urban crises. Previous research examining regeneration over significant periods of time in the UK and Ireland, suggests that often the same spaces and communities are subject to repeated rounds of intervention. In this paper, the thirty year trajectory of regeneration in Dublin Docklands is examined. The importance of global flows of capital and how they are mediated by local contexts, actors and institutions through roll-back, roll-out and roll-with-it forms of neoliberalisation are examined. Since the global financial crisis, neoliberal governmentalities have been more deeply embedded in place through new institutions and the formation of a new growth machine that has produced new vulnerabilities. Dublin Docklands has been successfully commodified and marketized through the sustenance, albeit changing, of a growth logic over more than 30 years. Yet significant challenges related to governance, social inclusion and spatial justice remain, and arguably have been (un-) intentionally co-produced in new forms by sustained rounds of state intervention.